Clinical and Histopathological Characteristics of Tumors Arising in Seborrheic Keratosis: A Study of 1365 Cases - Ye Q; Chen KJ; Jia M; Fang S (Dove Medical Press, 2021)
Qian Ye, Ke-Jun Chen, Meng Jia, Sheng Fang Department of Dermatology, The First Affiliated Hospital of Chongqing Medical University, Chongqing, 400016, People's Republic of ChinaCorrespondence: Sheng FangDepartment of Dermatology, The First Affiliated Hospital of Chongqing Medical University, No. 1 Youyi Road, Yuzhong District, Chongqing, 400016, People's Republic of ChinaEmail fangshengderm@163.comObjective: The aim of this study was to describe the clinical and histopathological characteristics of seborrheic keratosis (SK) with secondary tumor and identify associated factors.Methods: This study was a monocentric retrospective case-control study describing the factors associated with the development of tumors in SK. A total of 1365 patients with SK were admitted to our department between 2018 and 2021. All of the histopathological specimens and medical records of these patients were reviewed. We compared the data of 36 patients with tumors arising in SK with those of the remaining 1329 patients with only SK, which were designated the control group.Results: The incidence of tumors arising in SK that were biopsied was 2.6%. The tumor types included squamous cell carcinoma (SCC), basal cell carcinoma (BCC) and keratoacanthoma (KA). Compared with other patients with SK, elderly patients with immunosuppression, patients presenting surrounding erythema or ulceration, and those with SK in exposed areas had an increased possibility of developing a secondary tumor. Tumors arising within SK have the histopathological features of ulceration, cytologic atypia, mitosis, "malignant horn", trabecular cell cords, solar elastosis and severe inflammatory infiltration in the dermis.Conclusion: SK can show malignant progression in a small fraction of SK cases that are biopsied. This study is the first report on the clinical and histopathological characteristics of tumors arising in SK and identifies relevant factors in an Asian population.Keywords: seborrheic keratosis, tumor, clinical, histopathological